Ideas on Grading of Hardwoods for Pulping as Illustrated for the Forests of Bastar - Seth, V. K.; Kharbanda, B. C. (Indian Forester, 1973)
The pulp and paper industry in India has developed significantly during the last two decades and has to grow steadily during the coming years. With the growth of the industry the use of hardwoods as raw material has also been increasing. The need to evolve grading procedures for hardwood pulping material had been stressed at the Hardwood Conference which was held at Dehra Dun in 1971. This paper puts forward ideas on grading hardwoods for pulping and illustrates them by applying them to the forest resources of Bastar for whicb a good deal of inventory information is available. It bas been shown that at least 50 percent of the net available volume of the growing stock in the Sal, Teak and Miscellaneous Strata per hectare could be taken as belooging to the better grades of pulpwood. Similar studies could be done for different regions of the country and a national system of grading could be evolved. The effect of intensification of management, reduction of rotations and raising of fastgrowing plantations of pulpwood species on the production of better grades of pulpwood has also been examined. The need for evolving grading procedures or pulpwood would soon be felt both in the forestry and industrial sectors if it has not already been felt. Development of Pulp and Paper Industry in India.